Partial Validation of High Performance Liquid Chromatography for Analysis of Isoniazid in Rat Plasma - Novi Yantih; Siti Hafilah; Yahdiana Harahap; WAHONO SUMARYONO; Rianto Setiabudy (Fakultas Farmasi Universitas Pancasila, 2018)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Nicotinic acid derivatives such as isoniazid have the strongest anti-tuberculosis properties. For pharmacokinetics studying of isoniazid (INH), a method is needed to determine the levels of INH in plasma. Objective: The aim of this research is to partial validate of high performance liquid chromatography (HPLC) for analysis of INH in rat plasma. Method: For the preliminary study, rat plasma was used. The HPLC system used is a stationary phase C18 with length 250mm and temperature of 30°C, mobile phase hexane sulphonate acid 20mM pH 2.47–methanol (65:35). The analytical parameters in partial validated were linearity, lower limit of quantification (LLOQ), precision, accuracy, and recovery. Results: The results of linearity test of INH showed r value of 0.9996. LLOQ of this method was 0.1258μg/mL. The resulting accuracy and precision value met FDA requirements with a percent recovery ranging from 96.57–107.99%. Conclusion: The HPLC system was a valid method for analysis of INH in rat plasma.